Carbon dioxide utilization: process simulation of synthetic fuel production from flue gases - Batuhan Oztemel H.; Salt Inci; Salt Yavuz (Chemical Industry and Chemical Engineering Quarterly, 2022)
Environmental problems are on the rise and nowadays more climate-related, caused primarily by greenhouse gas emissions. Also, worldwide industrial emissions from power plants will cause 50% of the carbon dioxide concentration in the atmosphere by 2035. The simulation study of the synthetic fuel production from flue gas emitted by industrial power plants uses the ChemCAD Software. The study aims to reproduce all flue gas constituents into valuable products to reduce the effects of harmful gases on the environment. The synthetic fuel produced consists of 94.75% hydrocarbons with carbon numbers ranging from 1 to 4 with a 6.59% overall conversion rate. 95% of the sulfur content in flue gas is collected by desulfurizing the fuel mixture. The membrane process also recovers 90.3% of the nitrogen gas in the flue gas. Sulfurization, Reverse Water Gas-Shift, and Fischer-Tropsch syntheses have 95%, 79%, and 98.4% single-pass conversions, respectively, with appropriate catalysts. Economic analysis is also performed, and the payback period of the project is 6.1 years, while the return-on-investment rate is 16.64%.